Alternative Transition Of Potential Public Service Retribution Through The Services Of Regional Public Services Agency - Ihsanul Maarif (IHSA Institute, 2022)
The logical consequence of regional autonomy is that every regional government is obliged to improve efficiency and effectiveness in the administration of government and services to the community by utilizing regional resources. Regional taxes and regional levies, which are components of Regional Original Income (PAD), have good prospects for development. Therefore, regional taxes and regional levies must be managed professionally and transparently in the context of optimization and efforts to increase their contribution to regional income. The enactment of Law No.1 of 2022 concerning Financial Relations between the Central Government and Regional Governments, presents a restructuring or simplification of a number of regional taxes and regional levies. Regional taxes were restructured from 16 types to 14 types of taxes. Meanwhile, the object of regional retribution is simplified into 18 types of services from 32 types of services. The simplification of retribution has had an impact, especially on public service retributions, which lost 10 objects of retribution. In addition, the obligations of the Regional Government in providing public services to the community must be fulfilled. Among the many ways, the provision of public services can be fulfilled by the establishment of a BLUD. The implementation of BLUD by the Regional Government on user fees is often done. The simplification of user charges has a significant impact on the potential for PAD revenue. Moreover, many objects of public service retribution that are removed can become the basis for BLUDs as bodies that provide public services to local government delegates. The method used in this research is normative juridical, namely testing and reviewing secondary data. With regard to the normative juridical approach used, the research carried out through two stages, namely library research and field research which is only supporting. The results of the study show that the provisions related to the simplification of regional retribution by Law no. 1 of 2022 concerning HKPD, is dominated by changes in nomenclature, the abolition and addition of a number of objects of retribution. Elimination of retribution is not balanced with accountable supervision. The authority to establish BLUD is owned by the Regional Government in an attributive manner which is delegated to the UPT. The independence of BULD is reflected in the Government's desire to make BLUD a customer-oriented, not-for-profit-oriented and outcome-oriented organization. Conceptual changes and regulation of retribution have not reduced the problem of regional fiscal dependence. The simplified object of public service retribution needs to be optimized through BLUD services, in accordance with Permendagri No. 79 of 2019 concerning BLUD